INFORMATIONAL PECULIARITIES OF WAVEGUIDE DEFECTOSCOPY OF INTERNAL SURFACES - A. P. Markov; V. V. Potapkin; E. I. Marukovich; E. M. Patuk; A. V. Ivanov; A. G. Starovoitov (Литьë и металлургия, 2008)
The advantages and restrictions of the optical copying of inner surfaces with lightguide way systems are analyses.